"Glocal" neoliberal trends in Israeli education: The case of religionization. (July 2019) - Sabbagh, Clara
Abstract: As a political mechanism in Israeli education, statism ( Mamlachtiut ) has operated to enhance the nation-state's goals and ensure equality of opportunities. I demonstrate that global neoliberal trends have eroded the Israeli statist ( Mamlachti ) education system, giving rise to a new, partially privatized "quasi-market" educational platform. Within this dynamic, Israeli Education Ministry officials can be seen as actors determined to promote the privatization of the public education sphere, in contravention of the statist conceptions. While the intervention of the state in the Israeli public education sector is still ubiquitous, its role has been reframed and revised. Specifically, since the 1990s, and in particularly during the past decade, the state has encouraged and sponsored neo-conservative activities in public schools that have fostered religionization across the state-secular, religious and Haredi education sectors. This process threatens to undermine the fundamental precepts of Israeli democracy.